Links between household and family social dynamics with sleep profiles among BaYaka foragers of the Congo Basin. (October 2022) - Gettler, Lee T.; Samson, David R.; Kilius, Erica; Sarma, Mallika S.; Ouamba, Yann R.; Miegakanda, Valchy; Boyette, Adam H.; Lew-Levy, Sheina
Abstract: Given the contributions of sleep to a range of health outcomes, there is substantial interest in ecological and environmental factors, including psychosocial contexts, that shape variation in sleep between individuals and populations. However, the links between social dynamics and sleep are not well-characterized beyond Euro-American settings, representing a gap in knowledge regarding the way that local socio-ecological conditions interrelate with sleep profiles across diverse settings. Here, we focused on data from a subsistence-level society in Republic of the Congo to test for links between the household/family social environment and sleep measures. Specifically, we used actigraphy-derived sleep data (N = 49; 318 nights) from two community locations (a village and rainforest camp) among BaYaka foragers, who are members of a remote, non-industrialized subsistence society in the Congo Basin. We drew on social dynamics that have been previously linked to sleep variation in Euro-American contexts, including: household crowding, same surface cosleeping, and marital conflict. We examined the following sleep measures: total sleep time (TST), total 24-h sleep time (TTST), and sleep quality (fragmentation). BaYaka adults had shorter and lower quality sleep when their shared sleeping space was more crowded. In the village, parents with breastfeeding-aged infants had longer TTST and higher quality sleep than adults without infants, contrasting with results from other cultural contexts. Based on peer rankings of marital conflict, husbands showed longer and higher quality sleep in less conflicted marriages. Women showed the opposite pattern. These counter-intuitive findings for women may reflect the limitations of the measurement for wives' marital experiences. In total, these results point to the importance of considering local socio-ecological conditions to sleep profiles and underscore the need for expanded study of sleep and health outcomes in settings where shared sleep in constrained space is routine practice. Highlights: Sleep time and quality vary based on social environments in Euro-American contexts. We tested links between sleep and social dynamics among Congolese BaYaka foragers. Sleep time and quality were lower on nights with more crowded sleep conditions. Husbands had less quality sleep in marriages peer-rated as conflicted. The results highlight the importance of local socio-ecological conditions to sleep.